Topography of primitive reflexes in dementia: an F-18 fluorodeoxyglucose positron emission tomography study - Matias-Guiu, J. A.; Cabrera-Martín, M. N.; Fernádez-Matarrubia, M.; Moreno-Ramos, T.; Valles-Salgado, M.; Porta-Etessam, J.; Carreras, J. L.; Matias-Guiu, J. (European journal of neurology, 2015)
Background and purpose Although primitive reflexes (PRs) are inhibited during the first years of childhood, they may reappear with brain injury. PRs have been linked to frontal lobe dysfunction, but their precise topography has not yet been defined. The purpose of this study was to map which regions of the brain display a reduced glucose metabolism in patients with cognitive impairment and PRs. Methods A prospective study was conducted to evaluate PRs in a group of patients assessed due to suspected cognitive decline. Neurological and neuropsychological examinations and 18F‐fluorodeoxyglucose positron emission tomography fused with computerized tomography were performed. Voxel‐based brain mapping analysis by means of statistical parametric mapping was used to compare patients with and without PRs. Results The study included 99 patients (33 diagnosed with Alzheimer's disease, 33 on the frontotemporal dementia spectrum and 33 with other diagnoses). Mean age was 71 ± 9.7 years; time since symptom onset was 3.6 ± 2.9 years. At least one PR was observed in 43 cases (43.4% of the whole sample; 48.5% in the Alzheimer disease group, 63.6% in frontotemporal dementia and 18.2% in the group with other diagnoses). The group of patients with PRs exhibited a decreased cerebral metabolism in the bilateral superior frontal gyri (Brodmann area 6), bilateral putamina and thalami. Conclusions The presence of PRs was associated with hypometabolism at the superior frontal gyrus and putamen. This suggests that dysfunction in the corticostriatal motor circuit (supplementary motor area–putamen–thalamus) may constitute the anatomical basis of the recurrence of PRs.